Monthly variation in hog carcass traits - Mintert, J.; Dritz, Steven S.; Schroeder, Ted C.; Hedges, S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Little research has been conducted regarding the impact that time of year when hogs are marketed has on various carcass traits. This study examined monthly variation in a variety of hog carcass traits based upon 1995 slaughter summaries provided by a midwestern hog marketing network. Results indicate that carcass traits did indeed vary throughout the 1995 calendar year. However, given that these monthly variations were observed only during one year, it remains to be seen whether they indicate a seasonal relationship that hog producers can expect to see year after year or specific factors operative only in 1995. Additional years of data will be collected to extend this study and validate the results.
Keywords: Swine; Carcass traits; Monthly variation in carcass traits